2007
DOI: 10.2987/8756-971x(2007)23[124:ctatpe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Constant Temperature and Time Period Effects on Anopheles Gambiae Egg Hatching

Abstract: Anopheles gambiae Giles sensu stricto (Diptera: Culicidae) egg development and its relation to environmental parameters is an understudied aspect of vector biology. Although several studies have illustrated the dramatic effects of temperature on egg development, egg hatching dynamics remain unclear. The objective of this study was to expose An. gambiae eggs to various temperatures for different lengths of time and determine the impact on egg development and hatching count. Batches of mosquito eggs (n = 30 eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 15 publications
7
49
0
2
Order By: Relevance
“…Similarly, other study showed that limes were not hosts to the Caribbean fruit ßy (Hennessey et al 1992). Compared with host species, other conditions such as temperature and relative humidity make a greater impact on the egg incubation periods and viability (Impoinvil et al 2007, Mc Donnell et al 2007.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, other study showed that limes were not hosts to the Caribbean fruit ßy (Hennessey et al 1992). Compared with host species, other conditions such as temperature and relative humidity make a greater impact on the egg incubation periods and viability (Impoinvil et al 2007, Mc Donnell et al 2007.…”
Section: Discussionmentioning
confidence: 97%
“…Predicting how these environmental variables combine to mechanistically influence the suite of factors involved in resistance is clearly a complex problem. That said, not all environmental parameters will have equal effects on vector fitness, physiology and resistance; evidence 1418 (Supplementary information S1 (table)) suggests that temperature is a strong driver, whereas other variables can have little or no effect. Unravelling patterns and mechanisms from the complexity of natural systems requires an interdisciplinary perspective drawing on insights from ecology, immunology and molecular biology.…”
Section: Discussionmentioning
confidence: 99%
“…Second, mosquitoes are small-bodied, ectothermic insects. Many studies have already demonstrated that temperature can markedly affect diverse aspects of mosquito physiology and ecology, including the rate and viability of egg hatching 14 , the rate of development 15–17 , the propensity to feed and the rate of feeding 18 , and survival 15 . It would be surprising if immune function were any different.…”
mentioning
confidence: 99%
“…Data have been reported on the influence of adult temperature on adult survival [14][15][16][17][18]. Fewer data exist on the influence of juvenile environmental temperature on juvenile survival [19][20][21][22][23], but none exist, to our knowledge, on the influence of environmental temperature during the juvenile stages on adult mortality, although temperature throughout the mosquito's development may have repercussions on its survival [24].…”
Section: Introductionmentioning
confidence: 99%